2017
DOI: 10.1089/hgtb.2016.133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inverted Terminal Repeat Integrity on rAAV8 Production Using the Baculovirus/Sf9 Cells System

Abstract: Adeno-associated virus (AAV) inverted terminal repeats (ITRs) are key elements of AAV. These guanine-cytosine-rich structures are involved in the replication and encapsidation of the AAV genome, along with its integration in and excision from the host genome. These sequences are the only AAV-derived DNA sequences conserved in recombinant AAV (rAAV), as they allow its replication, encapsidation, and long-term maintenance and expression in target cells. Due to the original vector design, plasmids containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…First, the relative proportion of packaged capsids increased to 40% from 10%, and second, the packaging of non-specific sequences was reduced by 10-fold. [56] The incorporation of RBE in the original One-Bac1.0 was responsible for high-frequency co-packaging of rep/cap sequences in AAV capsids, confirming its role as a packaging signal. [50] Excision of the RBE component in the One-Bac2.0/AAV5 cell line resulted in more than 3-and 4-log reductions in the frequency of rep and cap sequence copackaging, respectively, with final rep/cap packaging levels reaching as low as 0.001% and 0.02%, respectively.…”
Section: Improved Efficiency and Specificity Of Vector Genome Packagingmentioning
confidence: 87%
See 4 more Smart Citations
“…First, the relative proportion of packaged capsids increased to 40% from 10%, and second, the packaging of non-specific sequences was reduced by 10-fold. [56] The incorporation of RBE in the original One-Bac1.0 was responsible for high-frequency co-packaging of rep/cap sequences in AAV capsids, confirming its role as a packaging signal. [50] Excision of the RBE component in the One-Bac2.0/AAV5 cell line resulted in more than 3-and 4-log reductions in the frequency of rep and cap sequence copackaging, respectively, with final rep/cap packaging levels reaching as low as 0.001% and 0.02%, respectively.…”
Section: Improved Efficiency and Specificity Of Vector Genome Packagingmentioning
confidence: 87%
“…The inverted terminal repeat sequence of the AAV genome is the only element from the wild-type AAV that is maintained in a recombinant vector and is present in cis in a transgene expression cassette. A recent report by Savy et al [56] showed that the unmodified AAV2 wildtype ITR (wtITR) sequence promotes enhanced and specific encapsidation of the rAAV8 vector sequence in contrast to truncated ITRs, which is found in traditional packaging plasmids such as pSUB201 and its variants. The latter was found to be responsible for non-specific packaging.…”
Section: Improved Efficiency and Specificity Of Vector Genome Packagingmentioning
confidence: 99%
See 3 more Smart Citations